Between Theocratic Republic and Democracy: Government Systems in Iran, the USA, and the UK - Arafat, Md. Yeasir; Sahed Siddiq; Anik Kumar Ghosh; Saurov Kumar Shil (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
From monarchs and presidents to supreme religious leaders, the architecture of power varies—but its essence shapes the fate of nations. This study presents a comparative analysis of the government systems of the Islamic Republic of Iran, the United States of America, and the United Kingdom. It focuses specifically on the structures and functions of the executive, legislative, and judicial branches in each country. While the USA and UK represent two distinct models of democratic governance—a federal republic and a constitutional monarchy respectively—Iran’s theocratic republic offers a unique blend of religious and political authority. Through a structured examination of institutional design, constitutional principles, and practical dynamics, this research reveals both convergences and contrasts among the three systems. The findings highlight how ideological foundations—secular liberalism in the West and Islamic jurisprudence in Iran—significantly shape institutional behavior and power distribution. The study concludes with reflections on the implications of these differences for governance, accountability, and the rule of law.